Floods in Pakistan; are pregnant women at a greater risk? - Warsi, Aimen; Mansoor, Noman (Journal of the Pakistan Medical Association, 2023)
Dear madam, The destructive floods in Pakistan have wreaked havoc, leading to increased mortality and morbidity rates among people. More than 1,100 people, including the excess of 350 children, have passed away, and the number is expected to grow [1]. The infrastructure is destroyed with no food or shelter. A halt in conveyance has made the necessities to life unattainable on people, and pregnant women are no exception. In Pakistan, about 500,000 pregnant women were affected by the 2010 floods, and 1.5 million women required emergency obstetric care [2]. Of the pregnant women during the disaster, 1,700 gave birth and hundreds suffered from complications during childbirth. Retained placenta, obstructed labour and fetal distress are some of the complications that pregnant women are at risk of during disaster. The scarcity of healthcare facilities and providers makes it difficult to manage maternal health problems, and delivery in these conditions often leads to maternal death [3]. The maternal mortality rate in Pakistan is 186 deaths per100,000, with rural areas having a 26% higher ratio [4]. Reproductive health is also affected by disasters through spontaneous abortion, birth defects, and low birth weight of babies [3] [5]. Pregnant women, breastfeeding mothers, and women with various disabilities have suffered the most. Sometimes women cannot express their problems which may lead to psychological issues. In addition, delay in transport and medical help affect maternal mortality in rural areas. Pakistan has limited healthcare resources in flood affected areas, making it difficult for pregnant women to help. An obstetrics field hospital must be established with trained staff with concerning disaster protocols. An experienced obstetrician should be taken on board to assess the emergency and set-up of prerequisite healthcare resources. Social media, mass media and public campaigns should be popularized to put an impact on this topic. Furthermore, public awareness for both genders and setting up medical camps in remote areas might help. Telecommunication must be established with field operators in coordination with other disaster relief providers to initiate the need of medicines like folic acid and other vitamins. Portable ultrasound must be arranged. The usage of alcohol-based cleanser instead of water to eradicate contamination. The impact that floods have on lives of pregnant women is an issue that is not given much attention. More studies are required in this area to understand the full extent of the problem.